2020
DOI: 10.3390/nu12092857
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Risk Factors for Malnutrition in Older-Aged Institutionalized Adults?

Abstract: Malnutrition is common in older adults and is associated with functional impairment, reduced quality of life, and increased morbidity and mortality. The aim of this study was to explore the association between health (including depression), physical functioning, disability and cognitive decline, and risk of malnutrition. Participants were recruited from nursing homes in Italy and completed a detailed multidimensional geriatric evaluation. All the data analyses were completed using Stata Version 15.1. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
2
25
2
Order By: Relevance
“…Table 1 displays a descriptive review of the included articles (n = 8), summarizing the impact of nutritional status on cognitive capacity and functional ability [ 8 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. No studies were found to be associated with alterations in nutritional status and prevention of polypharmacy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 displays a descriptive review of the included articles (n = 8), summarizing the impact of nutritional status on cognitive capacity and functional ability [ 8 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. No studies were found to be associated with alterations in nutritional status and prevention of polypharmacy.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the methods used as outcome measurements in the included papers. Five studies [ 8 , 30 , 33 , 35 , 36 ] used MNA (short or long form) to evaluate nutritional status, which used a standard <17 points (long form) or <7 points (short form) as a measure of nutritional status. One study used BMI (kg/m 2 ) to measure nutritional status [ 31 ], one used biochemical parameters, and another one used the geriatric nutritional risk index (GNRI) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Full agreement was observed in 75.7% of participants, with a kappa coefficient, a measure of agreement, of 0.44; this may be interpreted as "average" statistically significant agreement (p < 0.001). In their study of 246 older nursing home residents, Donini et al (2016) investigated agreement between nutritional status assessments made with the MNA, MNA-SF, MUST and NRS 2002. Agreement between the MNA and MUST or NRS 2002 was classified as "fair" (k = 0.270 and k = 0.291, respectively; p < 0.001).…”
Section: Discussionmentioning
confidence: 99%